PENGARUH LAYANAN JEMPUT BOLA PRODUK FUNDING TERHADAP DPK DAN JUMLAH NASABAH: STUDI PADA BPRS ARTHA KARIMAH IRSYADI - Hendri Triandini (ETIKONOMI, 2013)
The purpose of this study was to analyze the effect of funding product proactive service to the number of customers. Proactive services is considered as something superior to the BPRS Irsyadi in 2010, because the BUS not familiar with this system. But apparently once held more detailed testing using hypothesis testing and regression test dummy variables, the increase in deposits and a significant number of customers, not due to proactive services independently but other factors, the margins, and CAR. However, although the service is proactive not affect independently, the service is likely to proactive services into effect on the increase in deposits and the number of customers independently, if the system is further improved quality, both internal and external factorsDOI: 10.15408/etk.v12i2.1913